2005
DOI: 10.1086/428716
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and the Emergence of Role Differentiation in the Dynamics of Social Networks

Abstract: By means of extensive computer simulations, the authors consider the entangled coevolution of actions and social structure in a new version of a spatial Prisoners Dilemma model that naturally gives way to a process of social differentiation. Diverse social roles emerge from the dynamics of the system: leaders are individuals getting a large payoff who are imitated by a considerable fraction of the population, conformists are unsatisfied cooperative agents that keep cooperating, and exploiters are defectors wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
195
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(210 citation statements)
references
References 72 publications
9
195
0
6
Order By: Relevance
“…These spatial games, where the interactions are localized and non random, have been studied and extended in many ways (see, for example, Refs. [1,2,4,9,10,15,19,22,23,24,25,29,30,31,34,37,38,40,41,44,45,46,47,49,52]). Once the population is spatially structured, a natural question concerns the effects of mobility that, along with other important biological factors, is often neglected [28]: is it possible to evolve and sustain cooperation in a population of mobile agents, where retaliation can be avoided by moving away from the former partner?…”
Section: Introductionmentioning
confidence: 99%
“…These spatial games, where the interactions are localized and non random, have been studied and extended in many ways (see, for example, Refs. [1,2,4,9,10,15,19,22,23,24,25,29,30,31,34,37,38,40,41,44,45,46,47,49,52]). Once the population is spatially structured, a natural question concerns the effects of mobility that, along with other important biological factors, is often neglected [28]: is it possible to evolve and sustain cooperation in a population of mobile agents, where retaliation can be avoided by moving away from the former partner?…”
Section: Introductionmentioning
confidence: 99%
“…In all these cases, however, individuals cannot influence how often they will interact and how long particular interactions will last. On the other hand, other studies have explored the possibility of individuals meeting assortatively, by means of selective partner choice (Eshel and Cavalli-Sforza, 1982;Noë and Hammerstein, 1994;Skyrms and Pemantle, 2000;Bala and Goyal, 2001;Ebel and Bornholdt, 2002;Eguiluz et al, 2005;Biely et al, 2005) or by means of volunteering participation (Peck and Feld-man, 1986;Hauert et al, 2002;Szabó and Hauert, 2002;Hauert and Szabó, 2003;Aktipis, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the structure of interactions among individuals in real societies are seen to be described by complex networks of contacts rather than by a set of agents connected all-to-all [9,10]. Therefore, it is necessary to abandon the panmixia hypothesis to study how cooperative behavior appear in the social context.Several studies [11,12,13,14,15,16,17,18,19] have reported the asymptotic survival of cooperation on different kinds of networks. Notably, cooperation even dominates over defection in non-homogeneous, scale-free (SF) networks, i.e.…”
mentioning
confidence: 99%
“…Several studies [11,12,13,14,15,16,17,18,19] have reported the asymptotic survival of cooperation on different kinds of networks. Notably, cooperation even dominates over defection in non-homogeneous, scale-free (SF) networks, i.e.…”
mentioning
confidence: 99%